The relationship between esophageal cancer, chagasic megaesophagus and HPV: myths, tales or reality? - Munari, Fernanda Franco (2018)
A supposed role for persistent high-risk human papillomavirus (HPV) infection in esophageal squamous cell carcinoma (ESCC) etiology has been suggested by a number of studies. Concomitantly, megaesophagus induced by the Trypanosoma cruzi cell-cycle activity also shows a potential association with ESCC. This review discusses esophageal cancer and the potential association between chagasic megaesophagus and HPV as risk factors for ESCC development.